Part II – February 1968 - Papers - The Effect of Deformation on the Martensitic Transformation of Beta1 Brass - R. E. Hummel; J. W. Koger; V. Pasupathi (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1969)
Specimens of P1 brass were plastically deformed at room temperature to various degrees of deformation and subsequently cooled in order to transform them to low-temperature martensite. Deformation shifts Ms. A, , and the temperature of minimum resistivity to lower temperatures, and also decreases the temperature coefficient of electrical resistivity. These properties change rapidly up to about 15 pct reduction but vary very little with higher deformation. The possible relationships between martensite formed by deformation and the M, temperature of low-temperature martensite are discussed. Evidence is given that deformation martensite delays the formation of low-temperature martensite. BETA' brass undergoes at least two different types of martensitic transformations. One of these transformations (B1- B2) was first observed by Kaminski and ~urdjumov' and occurs when 81 brass with a zinc content between 38 and 42 wt pct (quenched from the single-phase region) is cooled below room temperature. Jollev and Hull' determined the structure of 0" from X-ray and electron-diffraction data as ortho-rhombic. Kunze came to the conclusion that the super-lattice cell of 0" is one-sided face-centered triclinic (pseudomonoclinic). The second martensitic transformation (B1-A1) occurs when the specimens are deformed at or somewhat above room temperature. This type of martensite will be called deformation martensite. Horn-bogen, Segmuller, and Wassermann4 determined the structure of deformation martensite to be bct. (An intermediate phase, az, occurs before the final phase appears.) At deformations higher than 70 pct, a, transforms into a.4 A critical temperature Md exists above which no transformation occurs during deformation and is estimated to be around 400°C in P1 brass.5 This martensite has elastic properties.6 When the sample is stressed, martensitic plates appear; when the stress is released, the plates disappear. The present paper studies the effect of deformation martensite on the formation of low-temperature martensite. The experiments involved samples of 8, brass which were plastically deformed by various amounts and were subsequently cooled below the transformation temperature. EXPERIMENTAL PROCEDURE The 13 brass investigated was made from 99.999 pct pure copper and 99.9999 pct pure zinc and contained 38.8 wt pct Zn. The specimens, consisting of foils 0.1 mm in thickness, were heat-treated at 8'70°C for 15 min in an argon atmosphere and then quenched into ice water. They were then deformed by cold rolling and subsequently cooled at a rate of 1°C per min. The martensitic transformation that occurred during cooling was followed by electrical resistivity measurements. The resistance measurement technique and its accuracy have been described in a previous paper. Because the transformation 81 —-8" occurs below room temperature, the samples were placed in a cryo-stat which contained isopentane as a cooling medium. The isopentane was cooled by liquid nitrogen pumped under pressure through a 15-ft coil of copper tubing which was immersed in the isopentane. The nitrogen flow was regulated by a temperature controller using two thermistors in the cooling medium. The cryogenic liquid could be heated with an immersion heater. The useful temperature range with this device was from +25° to approximately -155~C. EXPERIMENTAL RESULTS Resistivity Measurements. The following abbreviations are used in this paper to label the characteristic temperatures during the martensitic transformation. M, is the starting point of the martensitic transformation and is defined as that temperature where the resistivity vs temperature curve on cooling first deviates from a straight line. Mf is the temperature at which the martensitic transformation is completed. On reheating, the transformation from martensite to the parent phase starts at a temperature A, and ceases at a temperature Af. Fig. 1 presents five different resistivity vs temperature curves corresponding to the transformation of brass from Dl to 8" after different degrees of reduction in thickness. The following observations can be made from these curves. 1) With increasing degree of deformation the Ms temperature is shifted to lower temperatures. This shift ranges up to 35°C compared to the undeformed state. This is also indicated in Fig. 2, where AM, (the shift of Ms, compared to the undeformed state) is plotted vs the degree of deformation. AM, increases rapidly until a reduction of about 15 pct is reached. With higher deformations, no additional increase in AM, was found. 2) With increasing degree of deformation the temperature of minimum resistivity (M) is also shifted to lower temperatures. The shift, attains a maximum of about 61°C compared to the undeformed state. In Fig. 3, AM is plotted as a function of deformation. It can be seen that, as in 1 above, AM increases rapidly and no further shift of M occurs for deformations greater than 15 pct. 3) The temperature coefficient of resistivity, is given by the slopes (dp/dT) of the linear portions of